2016
DOI: 10.1007/s11033-016-3971-5
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol regulates angiotensin-converting enzyme and angiotensin converting-enzyme 2 in diabetic kidney disease

Abstract: To investigate the effects of calcitriol on angiotensin-converting enzyme (ACE) and ACE2 in diabetic nephropathy. Streptozotocin (STZ) induced diabetic rats were treated with calcitriol for 16 weeks. ACE/ACE2 and mitogen activated protein kinase (MAPK) enzymes were measured in the kidneys of diabetic rats and rat renal tubular epithelial cells exposed to high glucose. Calcitriol reduced proteinuria in diabetic rats without affecting calcium-phosphorus metabolism. ACE and ACE2 levels were significantly elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Furthermore, clinical features and pathological changes of lung tissues in the calcitriol‐treated LPS rats were remarkably milder than controls 67 . Lin et al 68 observed that calcitriol decreased ACE concentration and ACE/ACE2 ratio and enhanced ACE2 concentration in diabetic rats. In addition, calcitriol treatment remarkably suppressed p38 mitogen‐activated protein kinase and extracellular signal‐regulated kinase (ERK) phosphorylation, but not c‐Jun N‐terminal kinases phosphorylation, and effectively weakened ACE up‐regulation and ACE2 down‐regulation 68 .…”
Section: Interplay Between Vitamin D and Ace2: Proposed Potential Thementioning
confidence: 99%
“…Furthermore, clinical features and pathological changes of lung tissues in the calcitriol‐treated LPS rats were remarkably milder than controls 67 . Lin et al 68 observed that calcitriol decreased ACE concentration and ACE/ACE2 ratio and enhanced ACE2 concentration in diabetic rats. In addition, calcitriol treatment remarkably suppressed p38 mitogen‐activated protein kinase and extracellular signal‐regulated kinase (ERK) phosphorylation, but not c‐Jun N‐terminal kinases phosphorylation, and effectively weakened ACE up‐regulation and ACE2 down‐regulation 68 .…”
Section: Interplay Between Vitamin D and Ace2: Proposed Potential Thementioning
confidence: 99%
“…The AT1R antagonist candesartan, a well-accepted therapy in diabetic nephropathy, has recently been shown to improve renal tubular damage and albuminuria, partially through upregulation of ACE2/AT2R/Mas axis activity in the kidney [27•]. Conversely, treatment of diabetic rats with calcitriol reduced renal ACE levels and increased renal ACE2 expression, thus decreasing the ACE/ACE2 ratio, and associated with a reduction in proteinuria [54•]. Interestingly, in this study, reductions in ACE were mediated by the p38MAPK pathway, while ACE2 was upregulated via the ERK signaling pathway [54•].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Conversely, treatment of diabetic rats with calcitriol reduced renal ACE levels and increased renal ACE2 expression, thus decreasing the ACE/ACE2 ratio, and associated with a reduction in proteinuria [54•]. Interestingly, in this study, reductions in ACE were mediated by the p38MAPK pathway, while ACE2 was upregulated via the ERK signaling pathway [54•]. Systemic use of recombinant human ACE2 in diabetic mice similarly attenuated kidney injury while reducing blood pressure and decreasing NADPH oxidative activity [55].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…1,25-(OH) 2 D 3 acts as a negative regulator of renin gene expression via cAMP response element-binding protein (CREB) inhibition, which is required for the expression of renin [21]. In an experimental model of diabetic nephropathy, it was demonstrated that 1,25-(OH) 2 D 3 also has a suppressive effect on the expression of angiotensin converting enzyme 1 and 2(ACE), demonstrating the renoprotective action of in 1,25-(OH) 2 D 3 on the modulation of RAS [22]. The effects of the host 25(OH)D levels could extend beyond the macrophage, as lung epithelial cells have been demonstrated to express 1α-hydroxylase, and convert 25(OH)D into 1,25(OH) 2 D 3 leading to expression of cathelicidin [23].…”
Section: Vitamin D In Inflammationmentioning
confidence: 99%